Implementation of Maqasid al-Shariah Principles in the National Food Security System in West Kalimantan - Nurjannah, Syamratun; Hidayat, Samsul; Sari, Indah Purnama (Indonesian Journal for Entrepreneurial Review, 2025)
Food security is an important issue globally in regions such as West Kalimantan, it is strongly related to cultural, religious, and socio-economic factors. This research aims to evaluate and analyze the application of Maqhasid Shari'ah principles in the national food security system, with a focus on West Kalimantan province. This research uses secondary data with evaluation research type. The results show that the application of Maqhasid Shari'ah principles in the food safety system in West Kalimantan is still limited. While there are efforts to ensure food availability and accessibility, the integration of the principle of protection of mind and offspring still needs to be improved. Some policies have started to cover these aspects, but their implementation is not yet fully consistent and effective. This study recommends the need to strengthen the integration of Maqhasid Shari'ah principles in food safety policies and practices. A holistic approach combining legal, social and economic aspects can improve the effectiveness of the food safety system and provide wider benefits to society.